2020
DOI: 10.1177/2340944420941464
|View full text |Cite
|
Sign up to set email alerts
|

Net operating working capital and firm value: A cross-country analysis

Abstract: Here, we use a sample of firms from 30 countries during the period 1995–2013 to examine the relationship between net operating working capital (NWC) and firm value. Specifically, we show that the value of NWC varies across countries and that it depends on both investor protection and a country’s financial and economic development. Our findings imply that shareholders value NWC more in countries with strong enforcement of investor rights, and greater financial and economic development. Jel Classification: G15;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 57 publications
1
17
1
Order By: Relevance
“…In a global context, the problematics of working capital management represent an ongoing topic because of its importance in ensuring the optimal route for businesses. Being able to act as a buffer of liquidity (Baños-Caballero et al 2020), working capital plays a valuable role during economic turmoil (Enqvist et al 2014). In a recent report about all globally listed companies (PWC Annual Report 2019), PWC Global highlights that improving working capital may release €1.3 trillion of cash, which may boost capital investment by 55%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a global context, the problematics of working capital management represent an ongoing topic because of its importance in ensuring the optimal route for businesses. Being able to act as a buffer of liquidity (Baños-Caballero et al 2020), working capital plays a valuable role during economic turmoil (Enqvist et al 2014). In a recent report about all globally listed companies (PWC Annual Report 2019), PWC Global highlights that improving working capital may release €1.3 trillion of cash, which may boost capital investment by 55%.…”
Section: Introductionmentioning
confidence: 99%
“…However, empirical evidence on the relationship between working capital and corporate performance is rather mixed. On the one hand, investments in working capital are supposed to have a positive influence on firm profitability because they support growth in terms of sales and earnings (Baños-Caballero et al 2020;Aktas et al 2015). Sales are positively influenced by trade credit, improving customer relationships, while holding more inventories secures the business from the perspective of price fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, achieving wealth maximization for shareholders. Most of the previous studies confirmed the fact that WCM selected policy has an impact on its financial performance (Altaf and Ahmad, 2019;Baños-Caballero et al, 2019).…”
Section: Working Capital Strategies and Policiesmentioning
confidence: 64%
“…Deloof (2003), Garc ıa-Teruel and Mart ınez-Solano (2007), Ebben andJohnson (2011), Baños-Caballero et al (2012), Kieschnick et al (2013), and Afrifa and Padachi (2016) find a negative relationship between investment in working capital and company performance, as larger investments increase the probability of bankruptcy (Baños-Caballero et al, 2014;Humphrey, 2017;Le, 2019;Maheshwari, 2014). and Panigrahi (2017) recognise that investment in working capital increases a company's negotiating power with its providers, allowing it to obtain greater discounts, reduce supply costs, provide a hedge against input price fluctuations, and minimise loss of sales due to potential stock-outs, thus increasing the organisation's value (Aktas et al, 2015;Baños-Caballero et al, 2020;Deloof, 2003;Garc ıa-Teruel & Mart ınez-Solano, 2007). Therefore, maintaining an adequate investment in working capital allows for better company performance (Ukaegbu, 2014).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Thus, the challenge for companies in terms of managing working capital is to develop a culture that allows them to increase profitability (Anton & Afloarei Nucu, 2020). There is evidence of a positive and significant relationship between working capital and financial performance because working capital supports increases in sales (Aktas et al, 2015;Baños-Caballero et al, 2020;Mun & Jang, 2015). An increase in sales permits better management of commercial credit and inventories and helps firms avoid immobilisation of resources and price fluctuations (Mahmood et al, 2019).…”
Section: Introductionmentioning
confidence: 99%